To the 80th Anniversary of Gramicidin C Сreation: From the Study of the Asymmetry of Bacterial Molecules to the Discovery of Antimicrobial Peptides - B. G. Andryukov; N. N. Besednova; T. S. Zaporozhets (Антибиотики и Химиотерапия)
In 1942, G. F. Gause and M. G. Brazhnikova created one of the first antibiotics in the Soviet Union — gramicidin C. In the same year, its successful use started in front-line hospitals in the treatment of complications of wound infections. Thanks to it, the lives of hundreds of thousands of soldiers and officers were saved. Gramicidin C has passed the test of time, and today this antibiotic is effectively used in the treatment of infectious and inflammatory diseases, as well as purulent wounds. In this regard, the 80th anniversary is a good reason to recall the history of the creation of this peptide antibiotic possessing bactericidal action based on the presence of the D-isomer of the amino acid phenylalanine in the producing bacteria. However, the study of ways to overcome the spreading antibiotic resistance in bacteria, as well as the search for alternative antimicrobial strategies are currently on the agenda. For this reason, it is appropriate to recall that the study of the molecular structure of gramicidin C gave impetus not only to the discovery of a whole family of cyclic peptide antibiotics, but also to the discovery of the ability of various organisms to nonribosomal synthesis of biologically active peptides containing D-amino acids with a pronounced antimicrobial effect. Their development is already a vital task today, and the use of peptides is considered a real and promising alternative to traditional antibiotics. Thus, gramicidin C, obtained at the dawn of the era of antibiotics, became a harbinger of the birth of a fundamentally new and promising antimicrobial strategy.